2016
DOI: 10.1364/ao.55.003549
|View full text |Cite
|
Sign up to set email alerts
|

High diffraction efficiency of three-layer diffractive optics designed for wide temperature range and large incident angle

Abstract: A mathematical model of diffraction efficiency and polychromatic integral diffraction efficiency affected by environment temperature change and incident angle for three-layer diffractive optics with different dispersion materials is put forward, and its effects are analyzed. Taking optical materials N-FK5 and N-SF1 as the substrates of multilayer diffractive optics, the effect on diffraction efficiency and polychromatic integral diffraction efficiency with intermediate materials POLYCARB is analyzed with envir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 20 publications
0
5
0
1
Order By: Relevance
“…Therefore, it is necessary to design DOE for thermal aberration elimination in infrared refractive diffractive hybrid optical systems. DOE and refractive optical elements have different temperature characteristics, and the change in focal length is only determined by the material's expansion coefficient, and is not related to the change in refractive index caused by temperature changes [52]. In order to reduce the limitations of environmental temperature on DOE applications, the design goal is to achieve polychromatic integrated diffraction efficiency [53], which can improve the imaging quality of the imaging system.…”
Section: Infrared Imaging Systemmentioning
confidence: 99%
“…Therefore, it is necessary to design DOE for thermal aberration elimination in infrared refractive diffractive hybrid optical systems. DOE and refractive optical elements have different temperature characteristics, and the change in focal length is only determined by the material's expansion coefficient, and is not related to the change in refractive index caused by temperature changes [52]. In order to reduce the limitations of environmental temperature on DOE applications, the design goal is to achieve polychromatic integrated diffraction efficiency [53], which can improve the imaging quality of the imaging system.…”
Section: Infrared Imaging Systemmentioning
confidence: 99%
“…Virtual Conference 30 March-2 April 2021 extension of a diffractive lens and was already described in many papers. [12][13][14][15][16] This paper major results are the expression of the chromatic focal shift of MLDOEs and the study of their image quality.…”
Section: Icso 2020 International Conference On Space Opticsmentioning
confidence: 99%
“…In the frame of this analytical theory, the diffraction efficiency of MLDOEs reaches over 95% in the whole MWIR-LWIR bandwidth for on-axis incidence and any material combination [7,8]. On the other hand, off-axis incidence studies [9][10][11] have shown that an increase of the incident angle results in a loss of diffraction efficiency, which depends on the material combination. A widely used material selection method (MSM) [12] is based on the following observation: an "optimal" MLDOE design should undergo the smallest diffraction efficiency drop for the highest incidence angle.…”
Section: Introductionmentioning
confidence: 99%